Legal Construction of Fake Diploma Allegations: An Analysis of Electronic Data Integrity under the Personal Data Protection and Electronic Information Laws - Rijal Ibnu Sani; Suartini Suartini; Tri Cahya Indra Permana; Ahmad Ahmad; Misno Misno (Universitas Muhammadiyah Tangerang, 2024)
The discourse surrounding the validity of public officials’ diplomas in cyberspace is frequently entangled in the criminalization of defamation offenses. There exists a profound ambiguity in law enforcement practices that fail to distinguish between criticizing the validity of an electronic document and intending to attack an individual’s personal honor. This blurred boundary generates concern among citizens who seek to exercise social control over the integrity of educational data, yet are instead confronted with the excessive penal threats of the Electronic Information and Transactions (ITE) Law. This study aims to deconstruct the juridical status of diplomas as electronic data within the framework of the ITE Law and the Personal Data Protection (PDP) Law, and to examine the implications of Constitutional Court Decision No. 104/2024 for the legal protection of individuals who verify public data within the digital ecosystem. Method: This research employs a normative juridical method using statutory and case approaches to analyze the ratio decidendi of the Constitutional Court. Results: The findings demonstrate that, from a telematics law perspective, a diploma constitutes a set of electronic information characterized as an object of information or a digital asset. Based on the latest Constitutional Court ruling, a clear distinction is established whereby the object of defamation is limited to human beings as legal subjects possessing dignity and honor, rather than objects or documents. Conclusion: Juridically, questioning the integrity of diploma data cannot automatically be classified as defamation. As long as the statement focuses on the authentication and verification of the document, such conduct forms part of freedom of expression and the exercise of social control protected by law